Method for preparing polysaccharide-based emulsions for binding and coating applications
By grafting polyacrylate in hemicellulose derivatives to prepare hemicellulose-based hybrid emulsions, the problem of insufficient flexibility and adhesion of hemicellulose coatings is solved, and environmentally friendly binding and barrier properties are achieved, which is suitable for packaging and coating fields.
Patent Information
- Application Number
- JP2024540058
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-31
- Filing Date
- 2022-12-29
- Publication Date
- 2025-02-12
AI Technical Summary
Existing wood natural polymer coatings such as hemicellulose are difficult to provide sufficient flexibility and adhesion in binding or barrier film applications due to their high hydrophilicity and brittleness, and there is still a problem of insufficient flexibility after chemical modification.
The hemicellulose-based hybrid emulsion is prepared by grafting the hemicellulose derivative with the polyacrylate derivative, introducing an unsaturated bond, and by emulsion polymerization, the flexibility and hydrophobicity are improved.
The prepared hemicellulose-based emulsion has high flexibility, hydrophobicity and high transparency, suitable for packaging and coatings, replacing petroleum-based polymers and providing environmentally friendly binding and barrier properties.
Smart Images

Figure 2025504357000001 
Figure 2025504357000002 
Figure 2025504357000003
Abstract
Description
[Technical field]
[0001] The present invention relates to polysaccharide-based emulsions, in particular to novel polysaccharide-based emulsions and their use in binding and coating applications. [Background technology]
[0002] Latex (elastomer) is a soft, non-crystalline polymer, generally formulated as a water dispersion (latex), that is used in many products, such as paper, packaging materials, coatings, textiles, and automobile tires. Currently, commercially available products are oil-based, such as styrene-butadiene copolymers, styrene-acrylate copolymers, and polyvinyl-acetate copolymers.
[0003] Currently, fossil fuel-based polymeric materials for coating applications pose a major threat to the environment and human health. There is an increasing need for alternative bio-based polymeric materials to replace oil-based sources of materials.
[0004] However, wood-derived natural polymer coatings such as hemicellulose are very hydrophilic and brittle due to the presence of numerous hydroxyl groups and hydrogen bonds. Pure hemicellulose cannot provide sufficient flexibility and adhesion to be used as is for bonding and barrier film applications. Two main approaches have been used to prepare hemicellulose-based coatings. The first method is to physically mix hemicellulose with plasticizers such as glycerol, sorbitol, xylitol, or emulsifiers such as sucrose esters, palmitic acid, or polyvinyl alcohol. The physically mixed hemicellulose-based films are less brittle and exhibit better flexibility than pure hemicellulose-based films. However, the films are hydrophilic and vulnerable to water and moisture. Another method to prepare hemicellulose-based coatings is the chemical modification of hemicellulose based on oxidation, reduction, etherification, esterification, amination, fluorination, and crosslinking reactions. The resulting hemicellulose-based films can provide improved hydrophobicity, comparable to low-density polyethylene films, after modification. However, the flexibility (strain at break, stress) of films based on one-step chemically modified hemicellulose is still low, and such modified hemicelluloses often do not exhibit sufficient adhesive properties to be used as binders. Summary of the Invention [Problem to be solved by the invention]
[0005] (Summary of the invention) It is an object of the present invention to mitigate or entirely overcome the above-mentioned problems faced in the art. [Means for solving the problem]
[0006] The present invention provides polysaccharide derivatives, namely polysaccharide ethers grafted with poly(alkyl acrylates), which are obtained in particular by introducing groups containing unsaturation into the polysaccharide backbone via ether bonds and then reacting the derivatives exhibiting unsaturation with reactants bearing acrylate groups. The modified polysaccharides can be copolymerized, for example via emulsion polymerization, with specific poly(alkyl acrylates) to provide polysaccharide-based hybrid emulsions suitable for various end uses.
[0007] The polysaccharide-based emulsions are used in the paper, board and packaging industries, as well as in a wide range of coating and surface treatment products.
[0008] More specifically, the invention is defined by the features of the independent claims. Some particular embodiments are defined in the dependent claims.
[0009] According to a first aspect of the present invention, there is provided a polysaccharide ether grafted with poly(alkyl acrylate).
[0010] According to a second aspect of the present invention, there is provided a latex comprising a polysaccharide ether grafted with a poly(alkyl acrylate).
[0011] According to a third aspect of the present invention, there is provided a method for producing a bio-based emulsion comprising the steps of providing an allylated polysaccharide ether derivative and grafting the allylated polysaccharide ether derivative with a poly(alkyl acrylate).
[0012] According to a fourth aspect of the present invention, there is provided a bio-based emulsion formed by a method comprising the steps of providing an allylated polysaccharide ether derivative and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization.
[0013] According to a fifth aspect of the present invention, there is provided a bio-based film formed by a latex comprising a polysaccharide ether grafted with poly(alkyl acrylate), or an allylated polysaccharide ether derivative, and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization.
[0014] According to a sixth aspect of the present invention, there is provided a use of the latex.
[0015] More specifically, the invention is characterized by what is stated in the independent claims.
[0016] The present invention provides significant advantages.
[0017] In one embodiment, a bifunctional monomer such as allyl glycidyl ether having an epoxy group and a vinyl group is introduced and chemically bonded to a polysaccharide such as hemicellulose by etherification. The allylated polysaccharide is then grafted with an alkyl acrylate monomer to prepare a polysaccharide-based emulsion for coating applications, for example, using pre-emulsion semi-continuous emulsion polymerization.
[0018] The allylated polysaccharide ether derivatives exhibit good bonding properties, and films prepared therefrom have high flexibility with elongational strains of up to 30%, hydrophobicity with water contact angles of up to 117°, and optical transmittance of 92%. In the packaging industry, high transparency and low haze properties are desirable to ensure visibility of coated products. Thus, the allylated polysaccharide ether derivatives provide improved polysaccharide-based barrier coating compositions. The allylated polysaccharide ether derivatives of the present invention increase the flexibility of conventional polysaccharide-based barrier coatings, resulting in soft hemicellulose-based films.
[0019] A partial bio-based replacement of polyolefin-based latex in many industrial and end-user products is provided. Examples include use as binders in pigment coatings and paints, and barrier coatings for paper and paperboard, especially in food packaging and cosmetics. There is a clear need for new thermoplastic bio-based elastomers to replace the petroleum-derived synthetic polymers that are currently predominantly used.
[0020] Further features and advantages of the embodiments will become apparent from the following description of preferred embodiments which refers to the accompanying drawings. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic diagram of a synthetic route for a polysaccharide-based emulsion, in accordance with at least some embodiments of the present invention. [Diagram 2] 1 illustrates the hydrophobicity of polysaccharide-based films having different degrees of substitution based on water contact angle measurements, according to at least some embodiments of the present invention. [Diagram 3] 1 illustrates the flexibility of polysaccharide-based films having different degrees of substitution, according to at least some embodiments of the present invention. [Figure 4a] 1 shows the transparency and haze values of polysaccharide-based films having different degrees of substitution, according to at least some embodiments of the present invention. [Figure 4b] 1 shows the transparency and haze values of polysaccharide-based films having different degrees of substitution, according to at least some embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] (definition) As used herein, the term "bio-based" refers to materials that are derived from living organisms (biomass) and contain, consist of, or consist essentially of naturally occurring or synthetic substance(s).
[0023] As used herein, the term "average particle size" refers to the D of the cumulative volume distribution curve at which 50% of the particles, by volume, have a diameter less than that value. 50 Value, refers to.
[0024] As used herein, the term "about" refers to the actual given value, as well as approximations to the given value that would be reasonably estimated by one of ordinary skill in the art, including approximations based on experimental and / or measurement conditions for the given value.
[0025] Unless otherwise specified, properties experimentally measured or determined herein were measured or determined at room temperature.
[0026] Room temperature is 23°C unless otherwise stated.
[0027] Unless otherwise specified, experimentally measured or determined properties herein are measured or determined at atmospheric pressure.
[0028] As used herein, the term "unsaturated group" means that the group has one or more unsaturated bonds, such as double or triple bonds (where multiple unsaturated bonds may be conjugated or isolated), and may react with other groups, particularly other groups of a similar type. In one embodiment, the group has a double or triple bond.
[0029] According to one embodiment, a polysaccharide ether grafted with poly(alkyl acrylate) is provided.
[0030] According to one embodiment, the polysaccharide ether is obtained by grafting poly(alkyl acrylate) to the allyl ether groups on the polysaccharide. Thus, according to one preferred embodiment, the obtained allylated polysaccharide ether derivative consists of a water-soluble polymer having double bonds.
[0031] According to one embodiment, the poly(alkyl acrylate) is grafted to ether groups on the polysaccharide, the ether groups being obtained by reacting the polysaccharide with a bifunctional reactant having an epoxy group and an unsaturated group, in particular a vinyl or allyl group.
[0032] As used herein, the term "degree of substitution" (abbreviated as "DS") refers to the average number of substituents attached per anhydromonose unit of a polysaccharide.
[0033] According to one embodiment, the grafting with poly(alkyl acrylate) is achieved by polymerization, in particular radical polymerization, of alkyl acrylate monomers, in particular selected from the group of ethyl acrylate, n-propyl acrylate, isopropyl acrylate, and n-butyl acrylate, isobutyl acrylate, n-hexyl methacrylate, n-octyl methacrylate, and isooctyl acrylate, and n-butyl acrylate, and combinations thereof, in the presence of a polysaccharide ether. The monomers are selected from the group of monomers that produce homopolymers with low glass transition temperatures (e.g., glass transition temperatures between −80° C. and 20° C., such as −60° C. to 10° C. or −50° C. to 0° C.), and have long hydrophobic alkyl groups. “Long chain alkyl groups” refer to alkyl groups with 4 to 30 carbon atoms, in particular with 8 to 24 carbon atoms.
[0034] In other words, a bifunctional monomer, preferably having a reactive group and an unsaturated group, is used to react with the hydroxyl groups of the polysaccharide to introduce double bonds into the molecular structure of the polysaccharide. The modified polysaccharide is then copolymerized with poly(alkyl acrylate) via emulsion polymerization, such as pre-emulsion semi-continuous emulsion polymerization, to synthesize polysaccharide-based hybrid emulsions for end use.
[0035] In the present invention, the term "pre-emulsified semi-continuous emulsion polymerization" means a continuously operated emulsion polymerization process in which the monomers fed to the polymerization are pre-emulsified separately before being subjected to the polymerization reaction.
[0036] In one embodiment, a method for the synthesis of Galactoglucomannan (hereinafter "GGM")-based emulsions for binding and coating applications is provided. The first step is to introduce a bifunctional monomer having an epoxy group and a vinyl group by etherification reaction between the epoxy group and the hydroxyl group of GGM. The allylated GGM, which shows a certain degree of substitution of double bonds, is further copolymerized with an acrylic monomer. In particular, the copolymerization is carried out by a pre-emulsion semi-continuous emulsion polymerization method to prepare the GGM-based emulsion.
[0037] After casting and drying at room temperature, the resulting GGM-based films exhibit flexibility with elongational strains of up to 30%, hydrophobicity with water contact angles of up to 117°, and optical properties with transmittances of 90% or more, e.g., 92%. Furthermore, the use of GGM-based emulsions as binders has been demonstrated in a 1.5×1.5 cm2 film with a surface area of 1.5×1.5 cm2. 2 The hemicellulose derivatives were tested by gluing two pieces of wood of 1000g each. The tensile adhesive strength was found to be high. Thus, the hemicellulose derivatives appear to function as adhesives. The invention is also applicable to other structurally similar hemicelluloses or polysaccharides (e.g. xylans from wood and lower plants) and glucomannans from different sources.
[0038] FIG. 1 illustrates a synthetic route to a polysaccharide derivative latex according to at least some embodiments of the present invention, using galactoglucomannan as the polysaccharide and allyl glycidyl ether and n-butyl acrylate as exemplary reactants.
[0039] It is noted that in the sequence, the reactants and other components shown in Figure 1 may be replaced by other materials as described elsewhere. At least a portion of the synthetic process, and in particular the entirety, is carried out in an aqueous phase.
[0040] According to the synthesis route of FIG. 1, first, a GGM polymer is provided. This polymer contains 2-1000, usually about 5-100, monomers. C=C double bonds are introduced into the GGM backbone, particularly by graft polymerization, to prepare an allylated GGM with the appropriate degree of substitution that allows subsequent free radical copolymerization. This is achieved by carrying out an etherification reaction between the hydroxyl groups of GGM and the epoxy groups of allyl glycidyl ether (AGE) in an aqueous sodium hydroxide solution at a temperature of about 60° C. for about 10 hours under an inert atmosphere.
[0041] In the second step of the synthetic route, the unsaturated C=C double bonds of AGEs grafted onto the hemicellulose backbone are used as reactive sites for the free radical copolymerization of n-butyl acrylate (n-BA) in a semi-continuous emulsion polymerization process. The polymerization process is carried out at a temperature of about 80°C for about 4 hours in an inert atmosphere in the presence of ammonium persulfate initiator and sodium dodecyl sulfate surfactant. The final product of the polymerization process is a GGM-based emulsion.
[0042] The poly(alkyl acrylates), particularly n-butyl acrylate, can be derived entirely from biomass sources based on biobased alcohol fermented from glucose and biobased acrylic acid converted from lactic acid, resulting in a biomass content of up to 95% in the final product.
[0043] According to one embodiment, the polysaccharide has a degree of substitution of at most 1.5, in particular at most 1.0, for example about 0.04 to 0.83, 0.10 to 0.51, or 0.30 to 0.83, as determined by high pressure size exclusion chromatography using dimethylsulfoxide / lithium bromide as solvent and eluent.
[0044] According to one embodiment, the polysaccharide is selected from the group of starch, guar gum, and hemicellulose, and combinations thereof.
[0045] In one embodiment, the polysaccharide is derived from wood.
[0046] According to one embodiment, the polysaccharide is hemicellulose, in particular wood-derived hemicellulose.
[0047] According to one embodiment, the hemicellulose comprises galactoglucomannan, xylan, arabinogalactan, arabinogluconoxylan, xyloglucan, beta-glucan, alpha-glucan, or a combination thereof.
[0048] According to one embodiment, there is provided a latex comprising a polysaccharide ether grafted with a poly(alkyl acrylate) as described above.
[0049] According to one embodiment, the latex has a Z-average particle size of about 50-250 nm, e.g., about 100±20 nm, as measured by a Zeta-sizer Nano ZS90 laser nanometer particle size analyzer (Malvern, UK) using a 633 nm red laser.
[0050] The resulting polysaccharide-based emulsions contain or consist of at least 20%, preferably at least 40%, in particular up to 50% or more bio-based raw materials and exhibit good binding with other materials, water resistance, and high film flexibility and transparency. According to one embodiment, the latex has a content of bio-based raw materials of up to 95% by weight, preferably 70-95% by weight, in particular 75-95% by weight, for example 90-92% by weight, calculated on the solids of the latex, provided that the poly(alkyl acrylate) is obtained from bio-based raw materials.
[0051] According to one embodiment, the latex has a solids content of 10-50% by weight, measured from the weight of the total latex material.
[0052] According to one embodiment, there is provided a method for preparing a bio-based emulsion, comprising the steps of providing an allylated polysaccharide ether derivative and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization. According to one preferred embodiment, the method provides a one-step emulsion polymerization reaction between an allylated polysaccharide and an alkyl acrylate monomer, which is preferably a heterogeneous reaction between a water-soluble allylated polysaccharide and a water-insoluble alkyl acrylate monomer.
[0053] According to one embodiment, the allylated polysaccharide ether derivatives are obtained by reacting a polysaccharide with a bifunctional reactant containing an epoxy group and a vinyl group to chemically bond to the polysaccharide by etherification.
[0054] According to one embodiment, the difunctional monomer containing an epoxy group and a vinyl group is allyl glycidyl ether.
[0055] According to one embodiment, the method further comprises providing a polysaccharide ether derivative exhibiting an ether substituent with an allyl group with a degree of substitution of at most 1.5, in particular at most 1.0, for example about 0.04-0.83, 0.10-0.51, or 0.30-0.83, as measured by high pressure size exclusion chromatography using dimethylsulfoxide / lithium bromide as solvent and eluent.
[0056] According to one embodiment, the alkyl acrylate monomers are selected from the group of ethyl acrylate, n-propyl acrylate, and n-butyl acrylate monomers, and combinations thereof.
[0057] According to one embodiment, the polysaccharide has a number average molecular weight of 2,000 to 50,000 g / mol, preferably 5,000 to 20,000 g / mol, in particular 6,500 to 10,000 g / mol, and a weight average molecular weight of 2,000 to 100,000 g / mol, preferably 5,000 to 20,000 g / mol, in particular 10,000 to 35,000 g / mol, as measured by high performance size exclusion chromatography.
[0058] According to one embodiment, the allylated polysaccharide has a number average molecular weight of 2,000 to 50,000 g / mol, preferably 5,000 to 20,000 g / mol, in particular 6,500 to 10,000 g / mol, and a weight average molecular weight of 2,000 to 100,000 g / mol, preferably 5,000 to 50,000 g / mol, in particular 10,000 to 35,000 g / mol, as measured by high performance size exclusion chromatography.
[0059] According to one embodiment, the polysaccharide is selected from the group of starch, guar gum, and hemicellulose.
[0060] According to one embodiment, the hemicellulose is selected from the group of galactoglucomannan, xylan, arabinogalactan, arabinogluconoxylan, xyloglucan, beta-glucan, alpha-glucan, or a combination thereof.
[0061] According to one embodiment, said emulsion polymerization is carried out by semi-continuous emulsion polymerization, in particular by pre-emulsion semi-continuous emulsion polymerization.
[0062] According to one embodiment, the etherification of the polysaccharide is carried out under alkaline conditions, preferably at a pH between 8 and 12, more preferably at a pH between 10 and 12, in particular in an aqueous alkaline solution, such as an aqueous NaOH solution.
[0063] According to one embodiment, the etherification of the polysaccharide is carried out in an inert atmosphere, under alkaline conditions, in particular at a temperature between 30 and 90°C, for example between 40 and 75°C.
[0064] According to one embodiment, the method comprises the steps of adding sodium hydroxide to the polysaccharide, and after dissolution of the sodium hydroxide, adding a difunctional monomer such as allyl glycidyl ether in a molar ratio of 1:1 to 1:5 based on the anhydrous monosaccharide units, continuing the reaction under an inert atmosphere, for example for 0.5 to 24 hours, in particular for 5 to 12 hours, until the reaction is complete, and optionally neutralizing the reaction mixture with a mineral acid, for example hydrochloric acid or sulfuric acid.
[0065] According to one embodiment, the method further comprises filtering the allylated polysaccharide derivative using a membrane having a exclusion size of at least 500 Da, e.g., 12-14 kDa, to remove unreacted monomers, the filtering being carried out for 1-180 hours, e.g., 6-106 hours or 12-78 hours, such as about 72 hours, typically at room temperature.
[0066] According to one embodiment, the method comprises carrying out the grafting reaction in the presence of a surfactant, such as sodium dodecyl sulfate or sodium dodecyl sulfonate, added in an amount of, for example, 0.1-2.5 wt. %, in particular about 1 wt. %, based on the total weight of said alkyl acrylate monomers, optionally with further addition of a radical initiator, such as ammonium persulfate, potassium persulfate or sodium persulfate, in particular ammonium persulfate, potassium persulfate or sodium persulfate, in an amount of, for example, 0.5-2 wt. %, in particular 0.1-2.5 wt. %, for example 1 wt. %, based on the total weight of said alkyl acrylate monomers, and carrying out said reaction under an inert atmosphere, for example under a nitrogen atmosphere, at a temperature above 50° C., such as about 80° C., for 1-10 hours, for example about 4 hours.
[0067] Thus, according to one embodiment, the grafting reaction is carried out at a temperature above 50°C, such as about 80°C, preferably between 50 and 100°C.
[0068] According to one embodiment, an optional external surfactant, such as sodium dodecyl sulfate or sodium dodecyl sulfonate, forms micelles that act as additional reaction points to provide binding between the hydrophilic allylated polysaccharide and the hydrophobic alkyl acrylate monomers for polymerization.
[0069] According to one embodiment, the stirring speed during the grafting reaction is 500-2000 revolutions (r) / min, such as 1000-1500 revolutions (r) / min. In one embodiment, the stirring speed during addition and dissolution of the optional surfactant is 500-2000 revolutions / min. In one embodiment, the stirring speed before adding the optional surfactant is 1000-1500 revolutions / min.
[0070] According to one embodiment, the method further comprises casting and drying the formed emulsion into a film at 23° C. and 50% humidity for 48 hours.
[0071] According to one embodiment, there is provided a bio-based emulsion formed by the above method comprising the steps of: providing an allylated polysaccharide ether derivative; and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization.
[0072] According to one embodiment, there is provided a bio-based film formed by the above-described latex comprising a polysaccharide ether grafted with poly(alkyl acrylate) or by the above-described method comprising the steps of providing an allylated polysaccharide ether derivative and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization.
[0073] The hydrophobicity of the film is evaluated by the contact angle of a water droplet on its surface. According to one embodiment, the film has a hydrophobicity of 95 to 130°, preferably 105 to 120°, particularly 115 to 120°. The hydrophobicity is tested based on the water contact angle under the conditions of 25°C and 4 μL per droplet.
[0074] The transparency and haze values are tested with an ultra-visible spectrometer in the range of 300-800 nm. According to one embodiment, the film has a transmittance of 85-95%, preferably 90-92%, measured at a wavelength of 550 nm. The transmittance is measured by a Shimadzu UV-2600 spectrometer equipped with an integrating sphere attachment according to the ASTM D1003 standard test method. The measured wavelength range is 323-800 nm, and the corresponding value at 550 nm is selected for comparison.
[0075] According to one embodiment, the film has a haze value of less than 6%, preferably less than 5%, in particular less than 4%. The haze value is measured by a Shimadzu UV-2600 spectrometer equipped with an integrating sphere attachment according to the ASTM D1003 standard test method. The measured wavelength range is 323-800 nm, and the corresponding value at 550 nm is selected for comparison.
[0076] According to one embodiment, the thickness of the film is between 20 and 100 μm, preferably between 40 and 80 μm, in particular between 50 and 70 μm.
[0077] According to one embodiment, the water vapor permeability of the film is 0.10 to 0.50 g mm / (m 2 ·d·kPa), preferably 0.12 to 0.40 g mm / (m 2 ·d·kPa), especially 0.14~0.2g mm / (m 2 The water vapor permeability is evaluated according to the ASTM standard E96 / E96M-10.
[0078] The flexibility of the film can be determined by measuring the tensile stress and tensile strain. The flexibility is tested by cutting the film into a rectangle of 6 cm x 4 mm and mounting the film with a distance of 2 cm between the clamps. The film is stretched at a speed of 10 mm / min at room temperature. The thickness of the film is controlled to about 60 μm. Both the tensile stress and the tensile strain are affected by the degree of substitution during the polymerization reaction. After the introduction of the alkyl acrylate monomer in the second stage of the graft polymerization, the grafted polymer molecular chains become very long and flexible (which is determined by the nature of the molecular structure of the alkyl acrylate monomer), leading to an increase in the elongation at break without compromising the tensile stress. According to one embodiment, the tensile strain at break of the film is 15-40%, preferably 20-35%, in particular 25-30%.
[0079] According to one embodiment, the film has a maximum tensile stress of 20 to 40 MPa, preferably 25 to 35 MPa, in particular 28 to 32 MPa.
[0080] According to one embodiment, the film has good thermal stability. The film has two distinct decomposition stages. The first decomposition stage occurs at about 300°C, which is due to the decomposition of the polysaccharide polymer chains. The second decomposition stage occurs at about 420°C, which corresponds to the decomposition of the alkyl acrylate grafted polymer chains.
[0081] According to one embodiment, there is provided a bio-based binder formed by the above-described latex comprising a polysaccharide ether grafted with poly(alkyl acrylate) or by the above-described method comprising the steps of providing an allylated polysaccharide ether derivative and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization.
[0082] According to one embodiment, the binder is 1.5×1.5 cm 2When measured in a tensile test using two pieces of wood having a surface area of 100 mm or less, the wood has a tensile bond stress at break of 1 to 5 MPa, preferably 1.2 to 4.5 MPa, and particularly 1.5 to 4 MPa.
[0083] According to one embodiment, the latex as provided above is used in coating applications such as coating paper, paperboard, preferably food packaging and cosmetic packaging.
[0084] According to one embodiment, the latex provided above is used as a binder, such as a binder in pigment coatings or paints, or as an adhesive, such as an adhesive for bonding wood and wood products, or composite materials.
[0085] The following non-limiting example illustrates one embodiment. EXAMPLES
[0086] First, 10 g of hemicellulose-native GGM was dissolved in 100 mL of deionized water and stirred overnight at room temperature. The reaction system was equipped with a condenser, a magnetic stirrer with an oil bath, and a continuous flow of nitrogen. 2% sodium hydroxide was added to the GGM solution, and after dissolution of sodium hydroxide, different molar ratios of bifunctional monomer allyl glycidyl ether based on anhydromannose units were added and reacted at 60°C for 10 hours under nitrogen atmosphere. After cooling to room temperature, the above dispersion was 100% neutralized with dilute hydrochloric acid and monitored by pH electronic device.
[0087] Allylated GGM dispersions with different degrees of substitution, examined by quantitative 13C NMR spectra ranging from 0.30 to 0.83, were successfully prepared.
[0088] When the molar mass of GGM was greater than 12-14 kDa, the allylated GGM dispersion was used for dialysis for 72 hours with a dialysis membrane with a cutoff of 12-14 kDa to remove unreacted monomers. When the molar mass of the starting GGM was smaller than 12-14 kDa, a smaller cutoff dialysis membrane was used.
[0089] The above allylated GGM dispersion was transferred to a three-neck round-bottom flask and heated to 80°C. 1% sodium dodecyl sulfate based on the total weight of N-butyl acrylate was added to the flask and dissolved for 15 minutes, and 10 g of 30% of n-butyl acrylate was added for pre-emulsification with vigorous stirring for 15 minutes. Then, the remaining 70% of n-butyl acrylate and 1% ammonium persulfate based on the total weight of n-butyl acrylate were added dropwise with a peristaltic pump within 3 hours. The reaction system was further incubated for 1 hour to prepare the GGM-based emulsion.
[0090] The GGM-based emulsion was cast on a Petri dish and dried at 23° C. and 50% humidity for 48 hours to obtain a GGM-based film for barrier applications.
[0091] The hydrophobicity was tested for GGM-based films with different degrees of substitution based on the water contact angle at 25° C. and 4 μL / drop.
[0092] The flexibility was tested on GGM-based films with different degrees of substitution cut into 6 cm x 4 mm rectangles, and the films were mounted with a clamp distance of 2 cm. The films were stretched at a speed of 10 mm / min at room temperature. The thickness of the films was controlled at about 60 μm.
[0093] The transparency and haze values of GGM-based films with different degrees of substitution were tested with an ultra-visible spectrometer in the range of 300-800 nm.
[0094] The results of the above test are shown in FIGS.
[0095] In addition, the tensile adhesion strength of the latex was measured by a tensile test. 2The cross sections of two pieces of wood were coated with GGM-based emulsion. The bonded pieces of wood were left at room temperature for 10 hours before tensile testing. Tensile tests were performed on GGM-based latexes with degrees of substitution of 0.30, 0.51, and 0.83. The tensile bond stresses at break for the different latexes were 1.60 MPa, 2.32 MPa, and 3.78 MPa, respectively.
[0096] FIG. 2 illustrates the hydrophobicity of polysaccharide-based films with different degrees of substitution based on water contact angle measurements, according to at least some embodiments of the present invention.
[0097] The hydrophobicity of the film is evaluated by the contact angle of a water droplet on its surface. The hydrophobicity of GGM with a degree of substitution of 0.30, 0.51 and 0.83 is shown in Figure 2. The contact angle of GGM with a degree of substitution of 0.30 is 87°, the contact angle of GGM with a degree of substitution of 0.51 is 117°, and the contact angle of GGM with a degree of substitution of 0.83 is 98°.
[0098] In the case of GGM, the decrease in the water contact angle can be attributed to the surface roughness of the GGM film, because the contact angle can be affected by two main factors: polarity and surface roughness. With increasing AGE content, the hydroxyl groups attached to the hemicellulose backbone are more often replaced by the allyl groups of AGE, which means that a large number of C=C double bonds are grafted to the GGM molecular chains. For example, in a GGM product with a DS of 0.83, the heteropolymer of the allylated GGM with a higher DS is copolymerized with n-BA monomer to form a cross-linked and interpenetrating network between the molecular chains, resulting in the gel formation of the GGM product and the increased surface roughness of its film surface.
[0099] Figure 3 shows the flexibility of GGM-based films with different degrees of substitution based on tensile tests. Tensile tests showing the relationship between elongational (tensile) stress and elongational (tensile) strain are shown for films with degrees of substitution of 0.30, 0.51, and 0.83.
[0100] In general, the GGM film sample with an allylic degree of substitution of about 0.51 results in a film with optimal mechanical properties, i.e., ε of 31.2% and σ of 30.9 MPa. This is because, after the introduction of n-BA monomer in the second stage of graft polymerization, the molecular chains of the grafted polymer become very long and flexible (which is determined by the nature of the molecular structure of n-BA monomer), leading to an increase in the elongation at break without compromising the tensile stress.
[0101] In the GGM film with a high degree of allylation, the branched chains of hemicellulose are crosslinked and entangled with each other in the second polymerization stage, and the large amount of crosslinked network structure restricts the movement between and within the polymer chains, resulting in a decrease in the flexibility of the GGM film.
[0102] 4a and 4b show the transparency and haze values of polysaccharide-based films having different degrees of substitution, according to at least some embodiments of the present invention.
[0103] From Figure 4a, it can be seen that all the films have high transparency, especially at the wavelength of 550 nm. The C=C conversion rate has a slight effect on the transparency of the films. Also, all the films show a steep drop in the ultraviolet region, i.e., below 400 nm, indicating that the ultraviolet transmission is blocked. This result is very beneficial for the preservation of products in packaging coatings, since the most significant harmful effects of light are usually induced by ultraviolet light.
[0104] The haze value is used to quantify the percentage of forward light scattering. From Figure 4b, it can be seen that all the films have low transmission haze values. The higher the degree of substitution of the allyl group, the higher the polymerization density, which reduces light scattering, and therefore the haze value decreases.
[0105] It is to be understood that the disclosed embodiments of the invention are not limited to the particular structures, process steps, or materials disclosed herein, but extend to equivalents thereof recognized by one of ordinary skill in the relevant arts. It is also to be understood that the terminology used herein is used only for the purpose of describing particular embodiments, and is not intended to be limiting.
[0106] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearances of the phrases "in one embodiment" or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment.
[0107] As used herein, a plurality of items, structural elements, components, and / or materials may be presented in a common list for convenience. However, these lists should be construed as if each member of the list were individually identified as a separate and unique member. Thus, the individual members of such lists should not be construed as de facto equivalents of other members of the same list solely based on their presentation in a common group, unless otherwise indicated. Furthermore, various embodiments and examples of the invention may be referred to herein along with alternatives for its various components. It is understood that such embodiments, examples, and alternatives should not be construed as de facto equivalents of each other, but should be considered as separate and autonomous representations of the invention.
[0108] Furthermore, the described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, numerous specific details are provided, such as examples of lengths, widths, shapes, etc., to provide a thorough understanding of embodiments of the invention. However, one of ordinary skill in the relevant art will recognize that the invention can be practiced without one or more of the specific details, or with other methods, components, materials, etc. In other instances, well-known structures, materials, or operations have not been shown or described in detail to avoid obscuring aspects of the invention.
[0109] While the above examples illustrate the principles of the present invention in one or more specific applications, it will be apparent to those skilled in the art that numerous changes in form, use, and details of implementation may be made without the exercise of inventive faculty and without departing from the principles and concepts of the present invention. Accordingly, the present invention is not intended to be limited, except as by the scope of the claims set forth below.
[0110] The verbs "to comprise" and "to include" are used in this specification as open limitations that do not exclude or require the presence of features not recited. Features recited in the dependent claims are freely combinable with one another, unless otherwise expressly stated. Furthermore, it is to be understood that the use of "a" or "an", i.e. the singular form "a", "an", "the ... [Industrial Applicability]
[0111] The latexes and emulsions according to the invention can be used as adhesives, pressure sensitive adhesives and binders. In particular, they can be used as adhesives and pressure sensitive adhesives in wood based products such as plywood, or as binders in applications such as pigment coatings and paints. The films according to the invention can be used as films in packaging materials replacing aluminum foil, PE (Polyethylene), PP (Polypropylene), PVDC (Polyvinylidene chloride) or EVOH (Ethylene vinyl alcohol) for food, cosmetics, pharmaceuticals, or as barrier coatings for paper and paperboard. The latexes according to the invention can also be used in swim caps, chewing gum, mattresses, catheters, rubber bands, balloons, tennis shoes, and many other sporting goods. Another application is that the latex can be added to cement to resurface the cement surface or repair cracks.
Claims
1. Polysaccharide ethers grafted with poly(alkyl acrylates).
2. 2. The polysaccharide ether of claim 1, obtained by grafting allyl ether groups on the polysaccharide with poly(alkyl acrylate).
3. 3. The polysaccharide ether according to claim 1 or 2, wherein the poly(alkyl acrylate) is grafted to an ether group obtained by reacting a polysaccharide with a bifunctional reactant containing an epoxy group and an unsaturated group, in particular a vinyl group or an allyl group.
4. 4. The polysaccharide ether according to claim 1, wherein the grafting with poly(alkyl acrylate) is achieved by polymerizing, in particular radically polymerizing, in the presence of the polysaccharide ether, alkyl acrylate monomers, in particular alkyl acrylate monomers selected from the group of ethyl acrylate monomers, n-propyl acrylate monomers, isopropyl acrylate monomers, n-butyl acrylate monomers, isobutyl acrylate monomers, n-hexyl methacrylate monomers, n-octyl methacrylate monomers, and isooctyl acrylate monomers, and combinations thereof.
5. 5. The polysaccharide ether according to claim 1, having a degree of substitution of at most 1.5, in particular at most 1.0, for example from about 0.04 to 0.83, from 0.10 to 0.51, or from 0.30 to 0.
83.
6. 6. The polysaccharide ether according to claim 1, wherein the polysaccharide is selected from the group of starch, guar gum, or hemicellulose.
7. 7. The polysaccharide ether of claim 6, wherein the hemicellulose comprises galactoglucomannan, xylan, arabinogalactan, arabinogluconoxylan, xyloglucan, beta-glucan, alpha-glucan, or a combination thereof.
8. A latex comprising a polysaccharide ether grafted with the poly(alkyl acrylate) of any one of claims 1 to 7.
9. 9. The latex of claim 8 having a Z-average particle size of about 50 to 250 nm, for example about 100±20 nm, as measured by a Zeta-sizer Nano ZS90 laser nanometer particle size analyzer using a 633 nm red laser (Malvern, UK).
10. 10. The latex according to claim 8 or 9, provided that the poly(alkyl acrylate) is obtained from bio-based raw materials, having a content of bio-based raw materials of up to 95% by weight, preferably 50 to 95% by weight, in particular 75 to 95% by weight, for example 80 to 92% by weight, calculated on the solids of the latex.
11. 11. The polysaccharide ether according to any one of claims 8 to 10, having a solids content of 10 to 50% by weight.
12. A method for producing a bio-based emulsion, comprising the steps of: providing an allylated polysaccharide ether derivative; and grafting the allylated polysaccharide ether derivative with poly(alkyl acrylate) by emulsion polymerization.
13. 13. The method of claim 12, wherein the allylated polysaccharide ether derivative is obtained by reacting a polysaccharide with a bifunctional reactant containing an epoxy group and a vinyl group to chemically bond to the polysaccharide by etherification.
14. The method of claim 13, wherein the difunctional monomer containing an epoxy group and a vinyl group is allyl glycidyl ether.
15. 15. The method according to any one of claims 12 to 14, comprising providing a polysaccharide ether derivative exhibiting ether substituents with allyl groups with a degree of substitution of at most 1.5, in particular at most 1.0, for example about 0.04-0.83, 0.10-0.51, or 0.30-0.
83.
16. 16. The method of any one of claims 12 to 15, wherein the alkyl acrylate monomer is selected from the group of ethyl acrylate monomer, n-propyl acrylate monomer, isopropyl acrylate monomer, n-butyl acrylate monomer, isobutyl acrylate monomer, n-hexyl methacrylate monomer, n-octyl methacrylate monomer, and isooctyl acrylate monomer, and combinations thereof.
17. 17. The method according to any one of claims 12 to 16, wherein the polysaccharide has a number average molecular weight of 2,000 to 50,000 g / mol, preferably 5,000 to 20,000 g / mol, in particular 6,500 to 10,000 g / mol, and a weight average molecular weight of 2,000 to 100,000 g / mol, preferably 5,000 to 50,000 g / mol, in particular 10,000 to 35,000 g / mol, as measured by high performance size exclusion chromatography.
18. 18. The method of any one of claims 12 to 17, wherein the polysaccharide is selected from the group of starch, guar gum, and hemicellulose.
19. 19. The method of claim 18, wherein the hemicellulose is selected from the group of galactoglucomannan, xylan, arabinogalactan, arabinogluconoxylan, xyloglucan, beta-glucan, alpha-glucan, or combinations thereof.
20. 20. The process according to any one of claims 12 to 19, wherein the emulsion polymerization is carried out by semi-continuous emulsion polymerization, in particular by pre-emulsion semi-continuous emulsion polymerization.
21. 21. The process according to any one of claims 12 to 20, wherein the emulsion polymerization is carried out as a single-stage emulsion polymerization.
22. 22. The method according to any one of claims 12 to 21, wherein the etherification of the polysaccharide is carried out in an inert atmosphere, under alkaline conditions, in particular at a temperature of 30 to 90°C, for example 40 to 75°C.
23. 23. A method according to claim 22, comprising the steps of adding sodium hydroxide to the aqueous polysaccharide dispersion, adding, after dissolution of the sodium hydroxide, a difunctional monomer such as allyl glycidyl ether in a molar ratio of 1:1 to 1:5 based on the anhydrous monosaccharide units, continuing the reaction under an inert atmosphere, for example for 0.5 to 24 hours, in particular for 5 to 12 hours, until the reaction is complete, and optionally neutralizing the reaction mixture with a mineral acid, for example hydrochloric acid or sulfuric acid.
24. 24. The method according to any one of claims 12 to 23, further comprising filtering the allylated polysaccharide derivative using a membrane having an exclusion size of at least 500 Da, such as 12-14 kDa, to remove unreacted monomers, said filtering being carried out for 1 to 180 hours, such as 72 hours.
25. carrying out the grafting reaction by further adding a radical initiator such as ammonium, potassium or sodium persulfate, in particular 1% by weight of ammonium, potassium or sodium persulfate based on the total weight of the alkyl acrylate monomers, in the presence of a surfactant such as sodium dodecyl sulfate or sodium dodecyl sulfonate, added in an amount of, for example, 0.1 to 2.5% by weight, in particular about 1% by weight, based on the total weight of the alkyl acrylate monomers; 25. A process according to any one of claims 12 to 24, comprising carrying out the reaction under an inert atmosphere, e.g. under a nitrogen atmosphere, at a temperature above 50°C, such as about 80°C, for a period of 1 to 10 hours, e.g. about 4 hours.
26. 26. The method of any one of claims 12 to 25, wherein the method further comprises casting and drying the formed emulsion into a film at 23°C and 50% humidity for 48 hours.
27. 26. A bio-based emulsion formed by the method of any one of claims 12 to 25.
28. 27. A bio-based film formed by the latex of any one of claims 8-11 or by the method of any one of claims 12-26.
29. The bio-based film according to claim 28, wherein the film has a tensile strain at break of 15 to 40%, preferably 20 to 35%, in particular 25 to 30%.
30. 30. The bio-based film according to claim 28 or 29, wherein the film has a hydrophobicity with a water contact angle of 95 to 130°, preferably 105 to 120°, in particular 115 to 120°.
31. The bio-based film according to any one of claims 28 to 30, wherein the film has a transmittance measured at a wavelength of 550 nm of 85 to 95%, preferably 90 to 92%.
32. The bio-based film according to any one of claims 28 to 31, wherein the thickness of the film is from 20 to 100 μm, preferably from 40 to 80 μm, in particular from 50 to 70 μm.
33. The water vapor permeability of the film is 0.10 to 0.50 g mm / (m 2 ·d·kPa), preferably 0.12 to 0.40 g mm / (m 2 ・d・kPa), especially 0.14 to 0.2 g mm / (m 2 33. The bio-based film of any one of claims 28 to 32, having a modulus of elasticity of 1.0 -d-kPa.
34. The bio-based film according to any one of claims 28 to 33, wherein the film has a maximum tensile stress of 20 to 40 MPa, preferably 25 to 35 MPa, in particular 28 to 32 MPa.
35. 35. The bio-based film according to any one of claims 28 to 34, wherein the film has a haze value of less than 6%, preferably less than 5%, in particular less than 4%.
36. 27. A bio-based binder formed by the latex of any one of claims 8-11 or by the method of any one of claims 12-26.
37. The binder is 1.5 x 1.5 cm 2 37. The bio-based binder of claim 36, having a tensile bond stress at break of 1 to 5 MPa, preferably 1.2 to 4.5 MPa, in particular 1.5 to 4 MPa, as measured in a tensile test using two pieces of wood having a surface area of 1.2 to 4.5 MPa.
38. 27. Use of the latex according to any one of claims 8 to 11 or the bio-based emulsion obtainable by any of claims 12 to 26 in coating applications such as coatings for paper, paperboard, preferably for food packaging and cosmetic packaging.
39. 27. Use of the latex according to any one of claims 8 to 11 or the bio-based emulsion obtainable by any of claims 12 to 26 as a binder, such as a binder in pigment coatings or paints, or as an adhesive, such as an adhesive for bonding wood and wood products, or composite materials.
Citation Information
Patent Citations
Device for measuring swing of tooth
JP1978046199A
Polymer-based blend composition containing modified starch
JP1991056543A
Method and device for analyzing rotating degree ratio
JP1993066150A
synthetic bulk laxative
JP2004501197A
Heat-responsive polymer gel film
WO2010079680A1
Cited By
Adhesive composition and laminate
WO2026191957A1